Terapi Bermain Berpengaruh terhadap Kecemasan Anak yang Menjalani Kemoterapi - I Made Widastra; Eka Wahyu Ningsih; I Made Mertha (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
The purpose of this study was to determine the effect of play therapy on anxiety among children undergoing chemotherapy in Pudak Ward of General Public Hospital Sanglah Denpasar. This research is a pre-experimental research design with one group pre-test and post-test design. Sample consisted of 20 pediatric cancer patients were selected by purposive sampling, administered questionnaires to measure anxiety RCMAS anxiety then given play therapy. Based on the paired t-test results, obtained significant value (p) = 0.000 which is smaller than α = 0.05 (5%). It can be concluded that there is effect of play therapy on children’s anxiety who undergo chemotherapy in Pudak Ward of General Public Hospital Sanglah Denpasar.